The Presence of Salmonella in Sie Balu, Acehnese Dried Meat After Gamma Irradiation - Husna Husna; Nurliana Nurliana; Darmawi Darmawi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2017)
Sie balu is an Acehnese dried meat preserved by the addition of salt, acid and dried. However, long processing and drying it under the sun can cause meat products contaminated by Salmonella. Irradiation can eliminate Salmonella and other pathogenic bacteria in food. This study aims to determine the presence of Salmonella in sie balu after irradiated with increasing doses and 2 to 4 months shelf life. Sie balu was made of 5 kg fresh beef, dried under the sun to dry, vacuum and irradiated at doses of 5, 7 and 9 kGy. Salmonella was detected using bacteriological and biochemical tests. Results showed sie balu contaminated by Salmonella paratyphi B and Salmonella cholerasuis. The irradiation and shelf life significantly affect (P0.05) the count of Salmonella in sie balu compared with unirradiated one. Irradiation doses of 5, 7 and 9 kGy do not affect the count of Salmonella in sie balu. Extending the shelf life up to 4 months can increas the count of Salmonella. This study concluded that irradiated sie balu at doses of 5, 7 and 9 kGy can be stored for up to two months